Strategi Komunikasi Pemasaran Digital Kelompok Sadar Wisata dalam Membranding Pantai Pangasan sebagai Destinasi Wisata Populer - Salsabila, Chairunisya Zulfa; Amali, Muhammad Thoyib (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the digital marketing communication strategies implemented by the Tourism Awareness Group (Pokdarwis) in building the brand of Pangasan Beach as a popular tourist destination in Pacitan Regency. Using a descriptive qualitative approach and a case study method, data were collected through interviews, observations, and documentation. The AISAS model (Attention, Interest, Search, Action, Share) served as the main analytical framework. The findings reveal that Pokdarwis successfully attracted tourist attention through viral visual content on social media, generated interest through integrated digital strategies, facilitated information searches, encouraged visit decisions, and created ongoing promotional effects through user-generated content and electronic word of mouth (E-WOM). The synergy between digital and conventional promotion, along with the active involvement of the local community, proved effective in strengthening the positioning of Pangasan Beach as a sustainable cultural and nature-based tourism icon. These findings contribute to the development of marketing communication literature for community-based tourism destinations.